Economic Policy Uncertainty and Unemployment in the United States: A Nonlinear Approach - Giovanni Caggiano; Efrem Castelnuovo; Juan Manuel Figueres (Center for Economic Studies and ifo Institute (CESifo), 2018)
We model U.S. post-WWII monthly data with a Smooth Transition VAR model and study the effects of an unanticipated increase in economic policy uncertainty on unemployment in recessions and expansions. We find the response of unemployment to be statistically and economically larger in recessions. A state-contingent forecast error variance decomposition analysis confirms that the contribution of EPU shocks to the volatility of unemployment at business cycle frequencies is markedly larger in recessions.
Keywords: C32; E32; E52; 330; economic policy uncertainty shocks; unemployment dynamics; Smooth Transition Vector AutoRegressions; recessions; expansions